COMPOSIÇÃO FLORÍSTICA E ASPECTOS FÍSICOS DO CERRADO NOS CAMPOS GERAIS, PARANÁ - Ritter, Lia Maris Orth (2007)
The Campos Gerais, of the Parana State, Brazil, are the austral limit of occurrence of the domain Savannah in Brazil. Delimiting this region as studing area, they had been located and georreferenced 30 remainders of savannah, being then submitted to floristic and phytophysiognomies analysis. About 50% of the remainders sense presented physionomies of the "savannah stricto senso", distributed more to the north of the region, as well as the physionomies "cerradão" (13%), exclusive of the portions most northern. The “rupestre savannah” (17%) was more present to the long one of the reverse of the Devoniana Scarp, while the "campo sujo" (with fácies of savannah) presented more southern distribution, with 20% of the occurrences. The variable ambient had been selected for analysis: temperature, evapotranspiration, altimetry, declivity, angle of solar exposition, types of soil and linear distance of water´s courses, aiming at to detect a standard of current distribution. It was perceived for the analyses that some variables are overlapped. It can be explained by the biogeographic standard, that previously defined the original phytophysiognomies of the State, as well as the standard of current use, since this influences the savannah’s occurrence, composition and structure. After the data analysis was possible to note that, independently of the altimetry, when the declivities are smaller there´s a significant savannah absence, appointing to its replacement by pastures and farmings, restricting its permanence by areas evaluated as lesser economic value. The temperature, evapotranspiration and proximity with water´s courses, for this region, do not seem to act as ambient filter. A significant correlation was observed for soils, with clear preference of the savannah for litolic neosoils and latossoils.